Practical Implementation of an Indoor Robot Localization and Identification System using an Array of Anchor Nodes - AL-Forati, Israa Sabri A.; Rashid, Abdulmuttalib T. (Iraqi Journal for Electrical and Electronic Engineering, 2020)
This paper proposes a low-cost Light Emitting Diodes (LED) system with a novel arrangement that allows an indoor multi- robot localization. The proposed system uses only a matrix of low-cost LED installed uniformly on the ground of an environment and low-cost Light Dependent Resistor (LDR), each equipped on bottom of the robot for detection. The matrix of LEDs which are driven by a modified binary search algorithm are used as active beacons. The robot localizes itself based on the signals it receives from a group of neighbor LEDs. The minimum bounded circle algorithm is used to draw a virtual circle from the information collected from the neighbor LEDs and the center of this circle represents the robot’s location. The propose system is practically implemented on an environment with (16*16) matrix of LEDs. The experimental results show good performance in the localization process.